HISTOCHEMICAL ANALYSIS OF THE LEAVES OF FOUR ERICALES MEDICINAL PLANTS - Nurma Sabila; Siti Kusmardiyani; Muhamad Insanu (School of Pharmacy Institut Teknologi Bandung, 2022)
Active chemical compounds from medicinal plants are mostly secondary metabolites that can be histochemically tested. It enables the identification and localization of diverse secondary metabolites within the tissue, which is not possible with screening phytochemicals. In this study, the histochemistry of the leaf blades of Ericales plants i.e., cantigi (Vaccinium varingiaefolium (Blume) Miq.), persimmon (Diospyros kaki Thunb.), sapodilla (Manilkara zapota (L.) van Royen), and star apple (Chrysophyllum cainito L.) were evaluated. These species have been reported as folk medicines that have secondary metabolites. Each leaf tissue was observed under a microscope, and phytochemical compounds presence and location were detected by using specific reagents. The results showed that those four leaves contained phenols, flavonoids, and terpenes, while quinones were only found in cantigi leaves. The secondary metabolites were present in the idioblast of parenchymal and epidermal tissues. The persimmon and star apple leaves had secretory cavities in trichomes with terpenes and phenolic compounds.